The Impact of Manual Ability Level on Participation of Children with Cerebral Palsy in Life Areas: A Cross-Sectional Study - PASHMDARFARD, Marzieh (Iran J Child Neurol, 2019)
OBJECTIVES: Participation is a complex and context-dependent concept, which several factors can influence it. The aim of this study was assessing the relationship between the upper extremity function level of children with cerebral palsy (all type of cerebral palsy and severity) and their participation in different life areas. MATERIALS & METHODS: This cross-sectional study assessed the relationship between the level of upper extremity function of cerebral palsy children and their participation in different life areas. Participants were 274 parents of children with cerebral palsy of the schools of children with special needs and occupational therapy clinics in Tehran, Iran in 2018. They completed the Manual Ability Classification System (MACS) to determine the level of upper extremity function of children with cerebral palsy and Children Participation Assessment Scale-Parent version (CPAS-P) (to determine the participation level of children with cerebral palsy) questionnaires separately. RESULTS: The mean age of children was 8 yr and 8 months old (at least 6 yr and maximum 12 yr). The correlation between the level of upper extremity function and the overall score of each dimension of participation is significant (P<0.05) and moderate. CONCLUSION: The upper extremity function of children with cerebral palsy has a moderate and significant relationship with the participation of children with cerebral palsy in different life areas and with different dimensions of participation especially parental satisfaction dimension. Therefore, there is a correlation between upper extremity function and participation in occupations, but this relationship is moderate and is not very strong.